MAKNA SIMBOLIS TRADISI TAKIR MASYARAKAT DESA MULYOSARI, GEDANGAN, KABUPATEN MALANG - AISYAH; KHOLIK (Jurnal PENEROKA, 2025)
The takir tradition in Mulyosari village, Gedangan subdistrict, Malang district, is a Javanese tradition that is used at various traditional events such as celebrations, weddings, thanksgiving and so on. This research aims to describe the history of Mulyosari village, the symbolic meaning of the contents of the takir tradition, the cultural values ??contained in the takir tradition, and the role of the takir tradition in maintaining cultural preservation. The research location is in Mulyosari village, Gedangan subdistrict, Malang district. The research subjects used were resource persons or caretakers of the takir tradition in Mulyosari village, Gedangan subdistrict, Malang district. The method used is a qualitative descriptive method with field research. Data collection techniques use observation, interviews, documentation techniques and recording. The results of the research show that the takir tradition has various kinds of fillings including tumpeng combined with (side dishes), jenang abang and white jenang, telon flowers which include (roses, kenanga, pure white kanthil flowers), cok bakal which includes (young coconut, eggs, money), spices which include (shallots, garlic, chili, ginger, turmeric, laos, pepper, coriander, black pangium), kinangan which includes (betel, lime, gambier, jambe), teak leaves and two comb bananas. Each of the various traditional takir fillings has its own meaning as a symbol aimed at the good of society.